Liquid metal based flexible pressure sensor for tactile sensing of robots. Issue 5 (April 2021) - Chen, Ruiyang
Abstract: In contrast to circuit made by rigid material, flexible electronic devices are fabricated by flexible conductive material and have potential future in field of wearable electronic devices, biomedicine and intelligent sensor. Liquid metal is a kind of metal or alloy material that can remain liquid at room temperature. In recent years, it has been widely used in the field of stretchable electronics. This research applied adhesion different of liquid metal on different materials' surface to print liquid metal circuit of certain pattern on thermal transfer paper and trans-printed the circuit to flexible base to fabricate stretchable and flexible pressure sensor. In the research we tested the electrical property of pressure sensor and applied the results to tactile feedback research of intelligent robot. Not only does this liquid metal pressure sensor have simple structure and low in cost, but is suitable for large area and mass production. We believe this pressure sensor can be widely used in field of human-computer interaction and robot intelligent sensing.